AKUNTABILITAS PEMERINTAHAN DESA; Sebuah Telaah atas Perdes Nomor 01 Tahun 2011 tentang Biaya Administrasi Pelayanan di Desa Landungsari Kecamatan Dau Kabupaten Malang - Khoiron, Khoiron (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
Government bureaucracy is the most visible institutions to be monitored by the societies obviously at the village level, associated with the service. As a public institution, the village government is expected to actualize the future goals of the central government under President Joko Widodo called the concept of "nawa cita". Al elements of nation have to team up in setting up the nation on all fronts and sectors particularly public services; as a result of, rapid social transformation and the increasing complexity of the issues, encountered by the modern government. Those are prominent since the quality of public bureaucracy can be parameterized from the apparatus abilities degree in response to demands of the public. A qualified, accessible, and transparent service is the expectations and demands of society in almost all the world, including in Indonesia. Therefore, rejuvenation of the bureaucracy in the public service sector became a sort of a major reformation agenda in Indonesia since 1998 ago. Al in all, the encouragement to the improvement of reformation in service sector became a timeless expectation to be actualized. The society as users of services also must be good at monitoring; controlling and reporting if discomfort able thing occurred. For example practices of mal-administration, extortion and bribe public seemed to be a bureaucratic culture since long ago. Therefore, it required collective seriousness to carry out the reformation agenda to be accomplished with public expectations.DOI:Â https://doi.org/10.26905/pjiap.v1i2.503